2023
DOI: 10.1038/s41377-023-01083-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ion acceleration from transparency-driven foils demonstrated at two ultraintense laser facilities

Abstract: Laser-driven ion sources are a rapidly developing technology producing high energy, high peak current beams. Their suitability for applications, such as compact medical accelerators, motivates development of robust acceleration schemes using widely available repetitive ultraintense femtosecond lasers. These applications not only require high beam energy, but also place demanding requirements on the source stability and controllability. This can be seriously affected by the laser temporal contrast, precluding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…A dedicated pre-study was conducted, where the target thickness was varied over a wide range and the acceleration performance was compared to numerical simulations. An optimal target thickness between 200 − 300 nm was determined, where electron expulsion from the target bulk due to RIT led to extremely localised space charge fields [25]. These results served as the basis for the present study.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…A dedicated pre-study was conducted, where the target thickness was varied over a wide range and the acceleration performance was compared to numerical simulations. An optimal target thickness between 200 − 300 nm was determined, where electron expulsion from the target bulk due to RIT led to extremely localised space charge fields [25]. These results served as the basis for the present study.…”
mentioning
confidence: 98%
“…These advanced concepts enabled compact highintensity lasers with ultrashort pulses to achieve comparable performance levels with significantly reduced laser energy (few J) and repetition rates relevant for practical applications [18][19][20]. Recent experimental and theoretical results revealed that multiple acceleration mechanisms coexist during the laser-plasma interaction [21][22][23][24][25] and the current energy record for laser-driven proton acceleration near-100 MeV was achieved by a hybrid combination of processes [23], albeit still using a high-energy laser.…”
mentioning
confidence: 99%
See 3 more Smart Citations